The role of a leader in stimulating innovation in an organization - Katarzyna Kozioł-Nadolna (Administrative Sciences, 2020)
Many organizations seek ways to stimulate and encourage staff innovation. One ofthese is leadership that can boost staff innovation behavior. The aim of thisarticle is to reflect on leadership and its contribution to stimulating innovation. To achieve the aim of the article-and to verify the hypotheses-deductive inference, the analysis of the subject literature and the author's own questionnaire were used. The research was carried out with an original questionnaire to assess the role of a leader in stimulating innovative activity. The questionnaire consists of 28 statements.The analysis of the results of the empirical research has confirmed the research hypotheses that the role of a leader is to stimulate the creativity of employees and reward their innovative behavior.The analysis of the role of leadership in stimulating organizational innovation showed that the vast majority of statements concerning the role of leadership achieved a mean score above 5.0 (86%)-an average level. The research suggests that leaders should first and foremost play the following roles in stimulating innovation (e.g., a performer/creator of employee creativity and a promoter of rewarding the innovative behavior of employees).
Keywords: 350; innovation; innovation management; leader; leadership; stimulating innovation